Wydawnictwa literackie na Środkowym Nadodrzu od średniowiecza do XX wieku = Literary publishing houses in the Middle Oder region from the Middle Ages to the 20th century - Rudiak, Robert (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article examines the history of printing and publishing in the Central Oder region from the invention of printing until the end of the last century. The first printing house was established in Żary in 1588, followed by those in Żagań, Głogów, Kożuchów, and Krosno Odrzańskie. Throughout the 18th and 19th centuries, and until 1944, books were not published in the Central Oder region except for newspapers and pamphlets. The first books after World War II were published by the diocesan publishing house in Gorzów. This situation changed with the establishment of the Lubuskie Cultural Society in 1957. In subsequent years, books were published by institutions such as academic institutions, universities, libraries, museums, and regional societies, clubs, and community centers. After the fall of the Polish People's Republic, publishing houses such as LOW, AND, Pro Libris, Organon, Lamus, Arsenał, Akapit, Gest, Majus, Soravia, and E. Jarmołkiewicz proliferated. Fiction was published by institutions, associations and city and commune offices in Głogów, Drezdenko, Gubin, Wolsztyn, Choszczno, Skwierzyna, Zbąszyń, Świebodzin, Żary, and mostly in Zielona Góra and Gorzów Wielkopolski.
Keywords: drukarstwo; drukarze; wydawcy; historia; Głogów; Drezdenko; Gubin; Wolsztyn; Choszczno; Skwierzyna; Zbąszyń; Świebodzin; Żary; Zielona Góra; Gorzów Wielkopolski; printing; printers; publishers; history